2009
DOI: 10.1161/circinterventions.108.832048
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Clinical Consequences Associated With Sidebranch Occlusion During Stent Implantation Using Zotarolimus-Eluting and Paclitaxel-Eluting Coronary Stents

Abstract: Background-Myocardial infarction (MI) after drug-eluting stent placement has been associated with an unfavorable late prognosis. Although the etiology of periprocedural MI is multifactorial, sidebranch occlusion may be an important contributing factor. We sought to identify the incidence of sidebranch occlusion during zotarolimus-eluting stent (ZES) and paclitaxel-eluting stent (PES) placement and to relate sidebranch occlusion to the occurrence of periprocedural MI. Methods and Results-Angiograms were reviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 19 publications
4
35
1
Order By: Relevance
“…This relatively larger vascular footprint of the PES would potentially create a physical barrier to flow to the jailed side branch, resulting in ischemia and/or occlusion. A recent study observing higher rates of branch vessel occlusion after PES compared to a thinner profile zotarolimus-eluting stent supports stent profile as an important determinant of periprocedural myonecrosis [22]. Differences also exist in the polymer coatings of the two stents.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This relatively larger vascular footprint of the PES would potentially create a physical barrier to flow to the jailed side branch, resulting in ischemia and/or occlusion. A recent study observing higher rates of branch vessel occlusion after PES compared to a thinner profile zotarolimus-eluting stent supports stent profile as an important determinant of periprocedural myonecrosis [22]. Differences also exist in the polymer coatings of the two stents.…”
Section: Discussionmentioning
confidence: 96%
“…There are physical differences in profile of the two stents. The PES has a strut thickness of 132 microns, and a polymer thickness of 19.6 lm, while the EES has a strut thickness of 81 lm and a polymer thickness of 7.8 lm [21][22][23]. This relatively larger vascular footprint of the PES would potentially create a physical barrier to flow to the jailed side branch, resulting in ischemia and/or occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, in ENDEAVOR IV, of the 17 periprocedural non-Q-wave MIs after PES, 8 (47%) were large MIs with Ͼ10ϫ upper limit of normal creatine kinase-myocardial band rises. Other studies have indicated a higher than expected frequency of periprocedural MIs associated with PES implantation with a reported incidence of 3.5% to 5.4% (2,3) and post hoc angiographic analyses have suggested that disproportionate changes in PES covered side branches (both occlusion and/or reduced flow) may be partially responsible for these early clinical events (3,24).…”
Section: Discussionmentioning
confidence: 99%
“…25 These two DES differ in stent platform, which could have consequences for device flexibility and side branch access. 24 In addition, the DES use different coatings, which is reflected in their microscopic appearance. 13 Finally, both DES deliver different antiproliferative drugs.…”
Section: Discussionmentioning
confidence: 99%